Dog Stick Chewing: An Overlooked Instance of Tool Use? - Brooks, James; Yamamoto, Shinya (Frontiers in Psychology, 2021)
Tool use is a central topic in research on cognitive evolution and behavioral ecology in non-human animals. Originally thought to be a uniquely human phenomenon, many other species have been observed making and using tools for a variety of purposes, starting with Jane Goodall’s (1964) ground-breaking work with chimpanzees in Gombe. Despite the frequent attention and great research interest in animal tool use, and ubiquity of the behavior, we argue here that chewing sticks by dogs (and other animals) should be included as a case of tool use, suggesting tool use may be more common than is often assumed and that many cases of animal tool use may be overlooked.